2003
DOI: 10.1021/ar020154e
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Polypropionate Units and Heterocyclic Compounds by Cyclopropylcarbinol Ring-Opening with Mercury(II) Salts

Abstract: The mercury(II)-mediated electrophilic ring-opening reaction of various cyclopropylcarbinol derivatives bearing adjacent stereocenters and a remote nucleophilic functional group provides a useful strategy for synthesizing compounds bearing several contiguous stereocenters. These highly diastereoselective reactions occur with anchimeric assistance by the internal nucleophilic moiety and afford synthetically valuable building blocks such as polypropionate units or heterocyclic compounds. The application of cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 67 publications
1
15
0
1
Order By: Relevance
“…Regioselectivity was also examined: it is the less‐substituted CC bond of the three‐membered ring that reacts with the oxocarbenium ion (entries 6–8) 12. It is interesting to note that the major products 4 h and 4 i , obtained from 3 h 13a and 3 i ,13b are diastereomeric (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Regioselectivity was also examined: it is the less‐substituted CC bond of the three‐membered ring that reacts with the oxocarbenium ion (entries 6–8) 12. It is interesting to note that the major products 4 h and 4 i , obtained from 3 h 13a and 3 i ,13b are diastereomeric (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The combination of this transformation with the enantioselective Simmons–Smith cyclopropanation reaction of allylic alcohols and diastereoselective hydroboration/oxidation allowed access to various polypropionate derivatives 121 (Scheme ). , A useful feature of this transformation is the unique stereodivergence, opening a door for the synthesis of all stereoisomers of a given polypropionate unit. , It was later demonstrated that this reaction could be exploited for the synthesis of the naturally occurring ionophore zincophorin, where the key fragment was synthesized through an intramolecular oxymercuration ring opening of a cyclopropyl carbinol (Scheme ).…”
Section: Acid/base-mediated Ring Cleavagementioning
confidence: 99%
“…The 3-Methyl-phenol is mainly used in pesticides, medicine, perfume, resin plasticizer, film, antioxidant, and reagents [29][30][31]. Cyclopropyl carbinol is an intermediate used in chemical laboratory research and development of organic compounds and pharmaceuticals [32][33][34].…”
Section: The Py-gc-ms Analysismentioning
confidence: 99%